(untitled) (Acta Scientiarum. Health Sciences, 2024)
Type 2 diabetes mellitus (T2DM) has a high prevalence, with prospects for a significant increase. In 2021, T2DM caused one death every five seconds, most related to cardiovascular disease. Controlling cardiovascular risk factors (low-density lipoprotein [LDL-cholesterol] and blood pressure [BP]) significantly reduces these deaths. The objective of this study was to evaluate the prevalence of T2DM patients who have adequate BP and LDL-cholesterol control. Additionally we assessed the prevalence of patients who achieved the fasting blood glucose and glycated hemoglobin targets. We carried out a cross-sectional study in primary health care (PHC) units of the public health system (Sistema Único de Saúde - SUS) in the municipalities of Bernardino de Campos and Salto Grande, São Paulo State. Inclusion criteria were: diagnosis of T2DM, aged â‰¥ 18 years, attended by the PHC of these municipalities, who underwent a complete lipidogram examination within 12 months before the start of the study. Data were collected during home visits (age, sex, illnesses, drugs used, date and result of the last LDL-cholesterol, fasting blood glucose, and glycated hemoglobin laboratory tests, and the patients’ BP was measured). A total of 481 patients met the inclusion criteria and accepted to participate in the study, while 572 patients were excluded because they had not undergone a complete lipidogram within 12 months prior to the start of the study. Only 24.7 % of the patients had BP and LDL-cholesterol within the recommended target. It was verified that 148 patients (30.7 %) had fasting blood glucose and glycated hemoglobin within the target. A low rate of patients achieved the BP and LDL-cholesterol cholesterol targets, with an average interval between performing the last LDL-cholesterol test above the frequency recommended by the guidelines of the Brazilian Society of Diabetes.